Hydrothermally Synthesized CuCo2S4 Nanosheets as an Easily Accessible and Convenient Heterogeneous Catalyst for the Sonogashira Cross-Coupling Reactions - Soni, Kiran; Chauhan, Meenakshi; Deka, Sasanka (Frontiers in Materials, 2019)
A high surface area and the possibility of high charge separation and transportability make the two-dimensional (2D) nanomaterials very special in many applications, particularly in the field of catalysis. The usefulness of 2D nanomaterial is positively demonstrated in this study by employing it as an efficient heterogeneous catalyst in Sonogashira cross-coupling reaction, where the later one is well known for the formation of carbon–carbon bonds. 2D nanosheets of CuCo2S4 are synthesized using a hydrothermal synthesis and the average thickness of the sheets is found to be in the range of 10−15 nm. The transparent nanosheets are interconnected to form thick sheets and then aggregated to form a highly open three-dimensional hierarchical structure. This study explores the Sonogashira reaction very efficiently in water/ethanol at room temperature using hydrothermally synthesized CuCo2S4 nanosheets as catalyst for the C-C coupling reaction for the first time. The developed method is found to be economic, green, high yields, low catalyst loading and reusability of the catalysts. This present CuCo2S4 nanosheet heterogeneous catalyst afford the Sonogashira coupling of various aryl halides with terminal alkynes, giving a variety of aryl acetylenes in excellent yields and can be recovered by a simple filtration and reused for at least ten consecutive reactions with almost constant yield and activity.